2004
DOI: 10.1080/10473289.2004.10471015
|View full text |Cite
|
Sign up to set email alerts
|

Air Quality in Selected Megacities

Abstract: About half of the world's population now lives in urban areas because of the opportunity for a better quality of life. Many of these urban centers are expanding rapidly, leading to the growth of megacities, which are often defined as metropolitan areas with populations exceeding 10 million inhabitants. These concentrations of people and activity are exerting increasing stress on the natural environment, with impacts at urban, regional and global levels. In recent decades, air pollution has become one of the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 162 publications
(191 reference statements)
1
32
0
2
Order By: Relevance
“…Zhang et al 57 showed a significant association of the air quality index with mortality, especially in the winter and among those 55 years and older with COPD and other respiratory diseases. Similar findings, reported by Chang et al, 58 showed an increase of ϳ20% in mortality from COPD for an SO 2 increase of 100 g/m 3 and of ϳ3% in respiratory deaths for a TSP increase of 100 g/m 3 . Xu et al 54 collected 1990 data from a communitybased hospital in Beijing to assess the association of air quality with daily nonsurgery outpatient visits, and found significant associations with both SO 2 and TSP levels.…”
Section: Adverse Health Impactssupporting
confidence: 78%
See 1 more Smart Citation
“…Zhang et al 57 showed a significant association of the air quality index with mortality, especially in the winter and among those 55 years and older with COPD and other respiratory diseases. Similar findings, reported by Chang et al, 58 showed an increase of ϳ20% in mortality from COPD for an SO 2 increase of 100 g/m 3 and of ϳ3% in respiratory deaths for a TSP increase of 100 g/m 3 . Xu et al 54 collected 1990 data from a communitybased hospital in Beijing to assess the association of air quality with daily nonsurgery outpatient visits, and found significant associations with both SO 2 and TSP levels.…”
Section: Adverse Health Impactssupporting
confidence: 78%
“…A more detailed description of air quality management strategies applied in the nine case study cities is available as an online supplement to this review. 3 …”
Section: Introductionmentioning
confidence: 99%
“…Urban air quality is currently a global concern, which can be attributed to the massive scale of urbanisation and population growth, together with their resultant increases in traffic, industrialisation and energy use Molina et al 2004). It is understood that technological improvements in low emission motor engines have been offset by an exponential increase in vehicle numbers.…”
Section: The Needmentioning
confidence: 99%
“…Although not relying on sensors, such a service is already in place in London through the airText programme (http://www.airtext.info/). There is no reason why similar sensor-based programmes cannot be launched in cities with high pollution levels, such as those in Asia Peng et al 2014) or elsewhere (Molina et al 2004). …”
Section: The Needmentioning
confidence: 99%
See 1 more Smart Citation